2018
DOI: 10.3389/fonc.2018.00242
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Lead Concentration Is an Independent Predictor of Cancer Mortality in the U.S. General Population

Abstract: Lead is a ubiquitous pollutant that constitutes an environmental hazard worldwide. Although lead has been known as a carcinogenic factor in animal models, its role in human carcinogenesis is still a topic of debate with limited epidemiological evidence. Moreover, the association between urinary lead, as the most non-invasive and accessible way for lead measurement in human, and cancer mortality in general population has never been explored. We addressed this subject using continuous National Health and Nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…[Pb] u may, thus, be used as a proxy for [Pb] p . The utility of urine in monitoring Pb exposure has been illustrated in studies in Japan [ 193 ], Belgium [ 194 ], China [ 195 ], Thailand [ 12 ] and the U.S. [ 196 ]. In a Chinese study, workers in a lead–zinc mine had higher [Pb] u , [Cd] u and urinary 8-hydroxydeoxyguanosine, an indicator of oxidative stress, compared with those who worked in a steel smelting plant [ 195 ].…”
Section: Dosimetry and Nephrotoxicity Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…[Pb] u may, thus, be used as a proxy for [Pb] p . The utility of urine in monitoring Pb exposure has been illustrated in studies in Japan [ 193 ], Belgium [ 194 ], China [ 195 ], Thailand [ 12 ] and the U.S. [ 196 ]. In a Chinese study, workers in a lead–zinc mine had higher [Pb] u , [Cd] u and urinary 8-hydroxydeoxyguanosine, an indicator of oxidative stress, compared with those who worked in a steel smelting plant [ 195 ].…”
Section: Dosimetry and Nephrotoxicity Assessmentmentioning
confidence: 99%
“…This finding is reminiscent of studies relating E Cd to eGFR ( Section 4.3.2 ). In a follow-up study of 5316 participants in NHANES 1999–2010, [Pb] u levels > 1.26 μg/L were associated, respectively, with 1.79- and 6.60-fold increases in mortality from all causes and cancer [ 196 ].…”
Section: Dosimetry and Nephrotoxicity Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding lead carcinogenesis, a study investigating the association between urinary lead and cancer mortality showed that urinary lead levels were predictive of cancer-related death [93]. In contrast, a previous case-control study found no evidence of an association between urinary lead concentrations and breast cancer risk [94].…”
Section: Effects Of Lead and Cadmium On Cancer Immunology And Progressionmentioning
confidence: 99%
“…In case of Pb, human exposure occurs through ingestion or inhalation [14], it accumulates in bones and teeth [15] while excreted through the feces and also in the urine [16]. The half-life of lead, which is stored in bones, could be up to nearly 48 years, reflecting that it has a long-term effects on health [17]. Pb is considered as a carcinogen [18] and numerous studies have pointed out it is associated with hypertension [19], chronic kidney disease [20] cognitive and neuromuscular decline [21].…”
Section: Introductionmentioning
confidence: 99%